1999
DOI: 10.1159/000028877
|View full text |Cite
|
Sign up to set email alerts
|

Skull Base Growth in Craniosynostosis

Abstract: Although considerable scientific work has been published on the role of the skull base in craniosynostosis, the changes with age throughout childhood have not been fully outlined. The realisation that little attention has been paid to the posterior skull in craniosynostosis, resulted in renewed interest in skull base growth. The availability of computer-based image analysis provides a new accurate method of study in three dimensions. Using three-dimensional visualisation techniques, 34 points of the skull base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 22 publications
1
22
0
3
Order By: Relevance
“…Studies that included the cerebellum and PF consisted of cephalometric analyses of radiographs or CT scans. Those few studies that have focussed on the PF, presented a smaller anterior-posterior diameter in bicoronal craniosynostosis patients, suggesting its volume to be smaller (Richtsmeier et al, 1991;Sgouros et al, 1999). However, since the skull is deformed in craniosynostosis patients, the brain and cerebellum are deformed as a consequence.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that included the cerebellum and PF consisted of cephalometric analyses of radiographs or CT scans. Those few studies that have focussed on the PF, presented a smaller anterior-posterior diameter in bicoronal craniosynostosis patients, suggesting its volume to be smaller (Richtsmeier et al, 1991;Sgouros et al, 1999). However, since the skull is deformed in craniosynostosis patients, the brain and cerebellum are deformed as a consequence.…”
Section: Discussionmentioning
confidence: 99%
“…This condition can lead to altered venous drainage or higher intravenous pressure and hydrocephalus. In non-syndromic craniosynostosis, the skull base synchondroses are typically not involved 40. Nevertheless, regular follow-ups, including a hydrocephalus workup, should be mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In addition, animal studies have revealed that FGFR2 is expressed at the neural tube and cranial base during embryogenesis. [24][25][26][27] Several studies reported abnormalities of the skull 2,5,9,28,29 and skull base 9,13,30 in Crouzon syndrome in humans and in mice. [31][32][33] Thus, it is likely that FGFR2 gene mutations have an effect on hindbrain development and give rise to abnormal growth of its surrounding bone plates (i.e., the foramen magnum).…”
Section: Discussionmentioning
confidence: 99%